HOW TO WRITE A STRUCTURED ABSTRACT FOR RESEARCH ARTICLES - Ardriyati, Wienny; Widyaningrum, Agnes (Proceeding SENDI_U, 2015)
In every research article there is always presented an abstract of scientific paper. It is sometimes poorly written,often lack significant information. This article provides detailed suggestions with examples for writing thebackground, purposes, methods, result findings, and conclusions sections of a structured abstract. The purpose ofthis paper is to find out whether the writers can make a structured abstract and apply the five-move model.Themethod is toanalyze10 research articles of appliedlinguistics articles and 10 social articles.Each participant isanalyzed whetherhe / she has the structured based on a five-move model of each discipline.It is qualitative anddescriptive in nature. The result from applied linguistics corpusshows that only 2 out of ten participants apply thecomplete five-move model. From the social corpusonly one of the total participants applies the model. The rest ofthe participants from both disciplines cannot make a structured abstract, since they do not follow the model. It isexpected that the writers can write a structured abstract in their research articles with the proper five-move structure.Key words: abstract, significant, structured, move